Aislamiento de Escherichia coli en pollos de engorde con afección respiratoria y determinación de la sensibilidad frente a los antibióticos utilizados en el cantón Balsas, provincia de El Oro - Apolo Asanza, Janio Patricio (2015)
The purpose of this study was to evaluate the behavior of sensitivity and resistance of Escherichia coli strains isolated from chickens who presented respiratory symptoms and lesions compatible with colibacillosis in poultry from farms placed in canton Balsas in front of the commonly used antibiotics in poultry. Samples were plated on MaCconkey agar and the plates were incubated at 37 ° C for 24 hours. The identification of big and red colonies and turbid halo was necessary to identify the E. coli through biochemical tests. Bacterial isolates of 275 samples of the bird internal organs were performed, and the result was that 74.2% of the isolates were E. coli strains, 13.8% was negative and the remaining 12% belonged to other bacteria such as : citrobacter, enterobacter, proteus, and so on. Upon analysis of susceptibility it was found that all antibiotics studied showed frequency of resistance, and oxytetracycline with a 89. 5% was the one which showed increased resistance, followed by amoxicillin with a 78.4% and sulfametozazole + trimetoprim with a 71.1% . While the higher sensitivity was for the antibiotic of Gentamicine with a 71.6%, followed by Colistin with 51.5% with Florfenicol with 51.5%. It was also found that there is a high number of multi resistant strains of E. coli, from which 14% are low multi resistant, the 71.01% of them are medium resistant and the 14.7% has a high multi resistance.